1982
DOI: 10.1254/jjp.32.469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cl-1700 and Its Constituents on Acute or Chronic Gastric Lesions and Gastric Secretion in Rats

Abstract: Abstract-Effectsof CL-1700 (N-acetyl-L-carnosine aluminum) and its constituents, L-carnosine, N-acetyl-L-carnosine and AI(OH)3 on acute or chronic gastric lesions in intact rats and on gastric secretion in pylorus ligated rats were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In addition, we found that the effects of CL-1700 are much more potent than its constituents, L carnosine, N-acetyl-L-carnosine or AI(OH)3, to inhibit the development of different forms of induced acute gastric ulcers (2). The present experiment was done to determine whether CL-1700 also has an antiduodenal ulcer activity in two types of duodenal ulcer models in rats.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, we found that the effects of CL-1700 are much more potent than its constituents, L carnosine, N-acetyl-L-carnosine or AI(OH)3, to inhibit the development of different forms of induced acute gastric ulcers (2). The present experiment was done to determine whether CL-1700 also has an antiduodenal ulcer activity in two types of duodenal ulcer models in rats.…”
mentioning
confidence: 88%
“…in pylorus-ligated rats (2). Therefore, it is likely that CL-1700 exerted its antiduodenal ulcer effects partly through antisecretory and buffering pro perties.…”
mentioning
confidence: 99%